2021
DOI: 10.1002/ajmg.a.62568
|View full text |Cite
|
Sign up to set email alerts
|

Case report of atypical Leigh syndrome in an adolescent male with novel biallelic variants in NDUFAF5 and review of the natural history of NDUFAF5‐related disorders

Abstract: NDUFAF5 encodes a Complex I assembly factor which is critical to the modification of a core subunit, NDUFS7, in early Complex I factor assembly. Mutations in NDUFAF5 have been previously shown to cause Complex I deficiency leading to mitochondrial respiratory chain impairment. More than 15 individuals affected by variants in NDUFAF5 have been described; however, there is phenotypic heterogeneity within this cohort. Some individuals display features of classical Leigh syndrome with early onset neurodegeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Previous clinical reports of biallelic pathogenic variants in NDUFAF5 included mainly cases of classic Leigh syndrome with early-onset neurodegeneration or cavitating leukoencephalopathy in childhood at the severe end or cases developing progressive neurological deficits in early adulthood 10,11 . Bi et al reported on three siblings with bilateral striatal necrosis and bilateral lesions of the putamen in childhood 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical reports of biallelic pathogenic variants in NDUFAF5 included mainly cases of classic Leigh syndrome with early-onset neurodegeneration or cavitating leukoencephalopathy in childhood at the severe end or cases developing progressive neurological deficits in early adulthood 10,11 . Bi et al reported on three siblings with bilateral striatal necrosis and bilateral lesions of the putamen in childhood 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Unique manifestations and differences between the prenatal and postnatal presentation of the same genetic disorder have been described previously 10 and are likely to become more prevalent as additional cases are published 11 . Furthermore, variability in the phenotype of the same genetic disorder exists for many conditions, including NDUFAF5 ‐related disorders 3,12,13 . Dr Finsterer mentions other possible abnormalities in individuals with biallelic pathogenic variants in NDUFAF5 , including retinopathy and gastrointestinal abnormalities.…”
mentioning
confidence: 94%

Reply

Brabbing‐Goldstein,
Basel‐Salmon,
Yaron
2024
Ultrasound in Obstet & Gyne
“…Fifth, impairment of the visual pathways should be discussed. Given that NDUFAF5 variants can manifest phenotypically as Leber hereditary optic neuropathy (LHON) 2 or LHON plus 3 , it would be interesting to know whether optic atrophy was noted at autopsy 4 and whether loss or degeneration of retinal ganglion cells was detected on histological examination of the retina. NDUFAF5 variants can also present with gastrointestinal involvement 5 .…”
mentioning
confidence: 99%